Clinicopathological profile of breast cancer in young females at tertiary cancer center in Nepal - Pandey, Greta; Bhatta, Ranjan Raj; Upreti, Suraj; Dhungana, Ishan; Paudel, Bishow Ram (Nepalese Journal of Cancer, 2023)
Background: Breast cancer is one of the commonest cancer in females globally. The scenario in Nepal is also similar. Breast cancers are now not only limited to older age group but younger females are also visiting hospital with breast malignancies. An increase in trend of breast cancer in young females have been noticed. They are reported to have a more aggressive clinical and pathological features. Material and methods: We conducted a retrospective study of breast cancers in mastectomy specimen with focus on young females of less than or equal to forty years of age. The data collection period was from January 1st to December 31st 2021. Data were collected from the records of department of pathology. All those cases of post neoadjuvant chemotherapy with no residual masses microscopically and cases of male breast carcinoma were excluded. Results: A total of 273 cases of mastectomies were analyzed. 75 cases were from patients of ≤40 years of age and 198 belonged to age group of >40 years. Invasive breast carcinoma of no special type and histological (Nottingham Histological score) grade of Grade 2 was common in both groups. However grade 3 was more prevalent in younger group. Left breast was most frequent laterality for the cancer. Perineural invasion was found more in older females. Conclusion: Breast cancer is no longer a disease of older females only. More and more cases are being diagnosed at younger age group and they are more aggressive in them. Hence there is a greater need to spread awareness regarding breast cancer in the younger population as well.